Hamlet, Prince of Denmar - "Shakespeare, Willam" (Sweet cherry publishing: China, 2013)
Hamlet is one of the most popular tragedies of the legendary playwright, William Shakespeare. It tells the sad story of Hamlet, the Prince of Denmark, who, upon his father s death, returns from Wittenberg to discover the evil plot of his Uncle Claudius and his mother, Queen Gertrude. The play is focused around how Hamlet learns the truth about his father s death and seeks revenge. This short narrative version of the play has been suitably adapted to help introduce the play to young readers. It can be read by children or read to them by parents who wish to introduce them to the play. It can also be used by teachers as a classroom resource. The easy-to-read narration and comic-style illustrations are sure to captivate children s interest and develop their reading skills
Keywords: Adaptations Juvenile literature